STUDIES ON THE MEMBRACIDAE IV - PELAEZ, DIONISIO (Laboratorio Zapata, CD MEXICO, DF, MEX, 1944)
In 1939 the Department of Public Health reported 24 cases of undulant fever en Chihuahua; in 1940, 19; in 1941, 24; in 1942, 45; Jan to Apr 1943, 18 Most cases were probably due to Brucella melitensis since skin tests performed on several herds of goat
CIENC MEX
Keywords: STUDIES, MEMBRACIDAE IV; MULTIDISCIPLINARIA; BIOLOGIA DE INSECTOS; MORFOLOGIA DE LOS INSECTOS